2011
DOI: 10.1039/c0cp02075c
|View full text |Cite
|
Sign up to set email alerts
|

Use of polyols as particle size and shape controllers: application to boehmite synthesis from sol–gel routes

Abstract: Polyols were successfully used as size and shape controllers of oxide nanoparticles synthesized by soft chemistry in aqueous solution. The efficiency of acyclic polyols as a complexing agent depends obviously on the number of OH groups bonded to the carbon chain (and thus on the carbon chain length), but also on their stereochemistry. This innovating way to control morphology has been experienced for the synthesis of boehmite nanoparticles, whose morphology variations related to xylitol adsorption (C5 alditol)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
4
21
0
Order By: Relevance
“…Figure 1 shows the TEM images of the samples aged for the longest time: B0168, BM168, and BT168. Differences in the sizes of the particles can be easily noticed, evidencing restriction in growth induced by the additives, previously reported in a number of studies (Mathieu et al ., 2007; Chiche et al , 2009, 2011; Dash et al , 2010). In sample B0168 prepared with no additives prismatic particles with edges of lengths over 50 nm (some of them with rounded corners) were observed [Figure 1(a)].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the TEM images of the samples aged for the longest time: B0168, BM168, and BT168. Differences in the sizes of the particles can be easily noticed, evidencing restriction in growth induced by the additives, previously reported in a number of studies (Mathieu et al ., 2007; Chiche et al , 2009, 2011; Dash et al , 2010). In sample B0168 prepared with no additives prismatic particles with edges of lengths over 50 nm (some of them with rounded corners) were observed [Figure 1(a)].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that boehmite particle shapes commonly found, described as diamond-shaped platelets (Chiche et al , 2009), were not observed in samples BM168 and BT168; only in sample B0168 similar particles with round corners were visible. That particular morphology is mostly found at early stages of boehmite crystallisation, observed mainly when boehmite is prepared in basic aqueous media with relatively low temperatures or for short hydrothermal treatment times (Chen et al ., 2008; Jolivet et al , 2008; He et al , 2009; Chiche et al ., 2011). Within the samples of this study, this set of conditions were fulfilled by B024; Figure 2 shows TEM images of the samples prepared without additive in the different aging stages tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5a-c) and Rietveld analysis of the XRD patterns (Supplementary Table 2 and Supplementary Note 4). The latter shows that the average crystallite size along the [010] direction (so the stacking direction of the AlOOH layers) is considerably shorter than the in plane direction [001], which is the most typical signature of boehmite nanoplatelets as discussed in several articles [46][47][48][49] . Carbon, hydrogen and nitrogen (CHN) elemental analysis shows that the carbon content, and therefore the quantity of benzoate species attached to the particle surface generally increases with the reaction temperature (Supplementary Table 1 and Supplementary Note 1).…”
Section: Resultsmentioning
confidence: 99%
“…Boehmite can also be synthesized from liquid phase by hydrothermal/solvothermal routes 9,11,27,[40][41][42][43][44][45][46][47][48][49][50][51][52] or by sol-gel and precipitation techniques 8,[53][54][55][56][57][58][59] . Experimental conditions such as aluminum source, nature of the precipitating agent, pH, presence and nature of organic additives, temperature and time of thermal treatment (hydrothermal/solvothermal or thermal aging) may have a main influence in the resultant boehmite crystallite size and morphology…”
mentioning
confidence: 99%